Hepatitis B; Acquaintance and Prevention in Beauty Therapists, Peshawar - Rasool, Shaista; Gillani, Syed Imran; Afridi, Saira (Journal of Gandhara Medical and Dental Science, 2020)
OBJECTIVES: To assess the knowledge and practices of beauty therapists regarding hepatitis B virus. METHODOLOGY: A cross-sectional study conducted on beauty therapists of Peshawar. It was an interview-based questionnaire. Beauty therapists were investigated about hepatitis B transmission, vaccination, sterilization, use of gloves, and sterile equipment. Data was collected from most of the beauty salons of Peshawar. Data was analysed using SPSS 17. RESULTS: Around 90.6% therapists reported that they have knowledge about hepatitis B transmission by reuse of pointers (needles), 56.1% identified that vaccine can prevent hepatitis B, 98.7% beauty therapists that were interviewed reported exposure to blood during their work. 14.3% reported using gloves and 19.4% reported using only aprons. 20.4% of beauty therapists claimed sterilizing their instruments between clients, 51.4% reused needles whereas 88% reused orange sticks. CONCLUSION: Alertness about hepatitis and risks of transmission among beauty therapists is minimum, and their repetition of needles and inappropriate cleaning of tools is one of the reasons to spread hepatitis, which is widespread. KEYWORDS: Beauty Therapists, Hepatitis B, Transmission, Piercing, Barbers, Beauty Industry, Tattooist